2023
DOI: 10.1177/2050313x231193305
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of squamous cell carcinoma transformation in a mature cystic teratoma of the ovary

Candra Novi Ricardo Sibarani,
Hesty Duhita Permata,
Ellis Fasta Martiana
et al.

Abstract: Mature cystic teratoma of the ovary is the most common ovarian neoplasm (10%–20%). These tumors are generally benign but may undergo malignant transformation, 80% of which is squamous cell carcinoma, in postmenopausal women (1%–2%). Due to nonspecific findings, the preoperative diagnosis is challenging; most patients are detected at an advanced stage and have poor outcomes. A 40-year-old female, P2A0, complained of worsening lower abdominal pain and palpable abdominal mass. She had not been having menstrual pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The precise etiology of this malignant transformation is unknown [ 11 , 12 ]. Case reports indicate that those with malignant MCTO are usually between 40 and 55 years old, which is 10 years older than women with benign MCTO [ 5 ]. The average age of malignant transformation in MCTO was reported to be 53.5 years in previous investigations [ 12 ], although limited SCC cases have been documented in women as young as 19 years old [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The precise etiology of this malignant transformation is unknown [ 11 , 12 ]. Case reports indicate that those with malignant MCTO are usually between 40 and 55 years old, which is 10 years older than women with benign MCTO [ 5 ]. The average age of malignant transformation in MCTO was reported to be 53.5 years in previous investigations [ 12 ], although limited SCC cases have been documented in women as young as 19 years old [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, there are no specific clinical indications, serum markers, or imaging findings to diagnose MCTO transformation before surgery [ 14 ]. Some suggested, although nonspecific, risk factors for this condition are old age, postmenopausal state, increased tumor size and invasion, elevated levels of some tumor markers (CA125, CA19-9, and CEA), and tumor remnants [ 5 , 6 ], but the only way to confirm malignant transformation is through histopathologic study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Certain risk factors, such as tumor size, patient age, serum tumor markers level, and imaging results may increase the likelihood of malignant transformation [ 5 ]. Case reports have shown that malignant transformation of teratomas usually occurs in postmenopausal women, who are about 15 years older than women with conventional benign ovarian neoplasms [ 6 ]. Although most patients are asymptomatic, some may experience symptoms such as abnormal uterine bleeding, postmenopausal bleeding (PMB), abdominal pain, constipation, and a noticeable mass in the abdomen or pelvic area [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%